Ancylogastra, a new genus of Afrotropical Crambinae, with descriptions of seven new species (Lepidoptera, Pyraloidea, Crambidae) - Bassi, Graziano; Sáfián, Szabolcs; Léger, Théo; Müller, Günter C.; Kravchenko, Vasiliy D.; Poltavsky, Alexander N. (Zootaxa, 2021)
Ancylogastra Bassi & Poltavsky gen. n. is described to accommodate Cypholomia amphiaula Meyrick, 1934 (as A. amphiaula, comb. n.) and seven new species, all described and illustrated, as: A. boireaui Bassi & Sáfián sp. n., A. burundiana Bassi sp. n., A. coronata Bassi sp. n., A. endroedyi Bassi sp. n., A. gangraensis Bassi, Sáfián, Müller & †Kravchenko sp. n., A. ghanensis Bassi sp. n., and A. magnifica Bassi sp. n. Cypholomia Meyrick, 1933 is briefly discussed and C. crypsibela Meyrick, 1934 is transferred to Prionotalis Hampson, 1919 as Prionotalis crypsibela, comb. n.